On doubly warped products as gradient Ricci-Yamabe solitons - Karaca, Fatma (TAYLOR & FRANCIS LTD, 2026)
We characterize the gradient Ricci-Yamabe soliton of a doubly warped product manifold and provide a classification forWe further establish the conditions for the doubly warped product manifold to be a gradient Ricci-Yamabe soliton and demonstrate this result for a physical model of the universe, namely, for the doubly warped spacetime. Finally, we obtain a proper example for a gradient Ricci-Yamabe soliton for a doubly warped spacetime.
Keywords: Gradient Ricci-Yamabe soliton; doubly warped product; doubly warped spacetime; Mathematics